A New Funerary Epigram from Kibyra - Acar, Özge; Kokkinia, Christina (Tekmeria, 2022)
The Greek epigram published in this article was discovered in 2016 in modern Turkey, at Kibyra in southwest Asia Minor, during excavations under the directorship of Assoc. Prof. Şükrü Özüdoğru of the University of Burdur. Six lines preserving 3 elegiac distichs are carved on a stone that also features a relief showing a round shield with two greaves on either side. The epigram probably dates between the 1st century BCE and the 1st century CE and evokes the classical ideal of both physical and civic excellence in commemorating a man who died fighting as a citizen-soldier.